Red Light-Induced Systemic Resistance Against Root-Knot Nematode Is Mediated by a Coordinated Regulation of Salicylic Acid, Jasmonic Acid and Redox Signaling in Watermelon - Yang, You-xin; Wu, Chaoqun; Ahammed, Golam J.; Wu, Caijun; Yang, Zemao; Wan, Chunpeng; Chen, Jinyin (Frontiers in Plant Science, 2018)
Red light can stimulate plant defense against foliar diseases; however, its role in activation of systemic defense against root diseases remains unclear. Here, the effect of red light (RL) on root knot nematode Meloidogyne incognita (RKN) infestation was investigated in watermelon plants (Citrullus lanatus L.). Plants were exposed to 200 µmol m-2 s-1 photosynthetic photon flux density RL at the canopy level for 21 days using light-emitting photodiodes. The results showed that RL significantly suppressed gall formation and nematode development, which was closely associated with the RL-induced attenuation of oxidative stress in roots. Gene expression analysis showed that RL caused a transient upregulation of PR1 and WRKY70 transcripts at 7 days post inoculation in RKN-infected plants. Further investigation revealed that RL-induced systemic defense against RKN was attributed to increased jasmonic acid (JA) and salicylic acid (SA) content, and transcript levels of their biosynthetic genes in roots. Interestingly, while malondialdehyde content decreased, H2O2 accumulation increased in RL-treated RKN-plants, indicating a potential signaling role of H2O2 in mediating RL-induced systemic defense. Furthermore, analysis of enzymatic and non-enzymatic antidoxidants revealed that RL-induced enhanced defense agaist RKN was also attributed to increased activities of antioxidant enzymes as well as redox homeostasis. Taken together, these findings suggest that RL could enhance systemic resistance against RKN, which is mediated by a coordinated regulation of JA- and SA-dependent signaling, antioxidants, and redox homeostasis in watermelon plants.